Coexpression of PalbHLH1 and PalMYB90 Genes From Populus alba Enhances Pathogen Resistance in Poplar by Increasing the Flavonoid Content - Bai, Qiuxian; Duan, Bingbing; Ma, Jianchao; Fen, Yannan; Sun, Shujiao; Long, Qiming; Lv, Jiaojiao; Wan, Dongshi (Frontiers in Plant Science, 2020)
Secondary metabolites of the flavonoid pathway participate in plant defense, and bHLH and MYB transcription factors regulate the synthesis of these metabolites. Here, we define the regulatory mechanisms in response to pathogens. Two transcription factors from Populus alba var. pyramidalis, PalbHLH1 and PalMYB90, were overexpressed together in poplar, and transcriptome analysis revealed differences in response to pathogen infection. The transgenic plants showed elevated levels of several key flavonoid pathway components: total phenols, proanthocyanidins (PAs), and anthocyanins and intermediates quercetin and kaempferol. Furthermore, PalbHLH1 and PalMYB90 overexpression in poplar enhanced antioxidase activities and H2O2 release and also increased resistance to Botrytis cinerea and Dothiorella gregaria infection. Gene expression profile analysis showed most genes involved in the flavonoid biosynthesis pathway or antioxidant response to be upregulated in MYB90/bHLH1-OE poplar, but significant differential expression occurred in response to pathogen infection. Specifically, expression of PalF3H (flavanone 3-hydroxylase), PalDFR (dihydroflavonol 4-seductase), PalANS (anthocyanin synthase), and PalANR (anthocyanin reductase), which function in initial, middle, and final steps of anthocyanin and PA biosynthesis, respectively, was significantly upregulated in D. gregaria-infected MYB90/bHLH1-OE poplar. Our results highlight that PalbHLH1 and PalMYB90 function as transcriptional activators of flavonoid pathway secondary-metabolite synthesis genes, with differential mechanisms in response to bacterial or fungal infection.